Telaah Kodikologi dan Tekstologi pada Manuskrip Mushaf Al-Qur’an Raden Soleh Lamongan - Syania Nur Anggraini; Muhammad Makmun (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
This article examines the manuscript of Mushaf al-Qur’an Raden Soleh, which is found in Drajat village, Lamongan. The manuscript is quite interesting as it has illuminations that combine the Sumatran-Maluku style with Majapahit-Demak style tendrils. However, the various decorative ornaments in it do not leave the Javanese elements. This paper will specifically examine the manuscript from the aspects of codicology and textology. The findings of this article are twofold: First, from the codicological aspect, this manuscript uses European paper, with a watermark of the type of lions that reads GOD ZY MET ONS, also a countermark that reads VDL, written in black and red ink, and uses khat naskhī hāshimī. Secondly, from the aspect of textology, several scholia were found, such as error correction, additional memorization, letter description, alternate words, and initial juz instructions. In addition, this manuscript also includes various qiraat of the Qur’an. Although it is dominated by the qiraat of Imam ‘Āṣim narrated by Ḥafṣ, this mushaf also records several qiraat from other scholars. This manuscript is also found to be corrupt in several parts, including errors in writing sentences, words, letters, or harakat. On the other hand, this manuscript also has uniqueness, including the writing of surah al-Fātiḥah in the opening and closing of the mushaf.